2006
DOI: 10.1186/bcr1370
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive copy number profiles of breast cancer cell model genomes

Abstract: Introduction Breast cancer is the most commonly diagnosed cancer in women worldwide and consequently has been extensively investigated in terms of histopathology, immunochemistry and familial history. Advances in genomewide approaches have contributed to molecular classification with respect to genomic changes and their subsequent effects on gene expression. Cell lines have provided a renewable resource that is readily used as model systems for breast cancer cell biology. A thorough characterization of their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
85
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 50 publications
14
85
1
Order By: Relevance
“…Moreover, amplification of 1q has frequently been detected in many other solid tumors, including breast, ovarian, prostate, and lung tumors [37][38][39][40]. In our previous study, a focal amplified region has been narrowed down to 1q24.1-24.2, suggesting the existence of a cancer gene at this amplicon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, amplification of 1q has frequently been detected in many other solid tumors, including breast, ovarian, prostate, and lung tumors [37][38][39][40]. In our previous study, a focal amplified region has been narrowed down to 1q24.1-24.2, suggesting the existence of a cancer gene at this amplicon.…”
Section: Discussionmentioning
confidence: 99%
“…The BLBC specimens and MDA-MB-231 were assayed using an SMRT aCGH platform as previously described (Shadeo and Lam, 2006;Stratford et al, 2007). To be classified as gain, there has to be a probability >80% (determined by Hidden Markov Model algorithm) and >0.15 log 2 ratio (determined by aCGH-Smooth software).…”
Section: Immunoblotsmentioning
confidence: 99%
“…One could argue that high levels of MET may be due to gene amplification. To begin to address this, we performed comparative genomic hybridization on MDA-MB-231 and reported that amplifications were not found in the 7q31.1 where the MET gene resides (Shadeo and Lam, 2006). Similarly, MET is not commonly amplified in primary BLBC based on the analysis of 10 tumors (Supplementary Figure 2).…”
Section: Yb-1 Induces Met In Blbcmentioning
confidence: 99%